2014
DOI: 10.1037/a0032586
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy support, self-regulation, and weight loss.

Abstract: Objective Social support is believed to contribute to weight loss success, yet the type of support received is rarely assessed. To develop more effective weight loss interventions, examinations of the types of support that are associated with positive outcomes are needed. Self-Determination Theory suggests that support for an individual’s autonomy is beneficial and facilitates internalization of autonomous self-regulation. We examined whether autonomy support and directive forms of support were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
106
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 45 publications
15
106
0
4
Order By: Relevance
“…Chapter 5 Qualitative study with health professionals T his study presents a qualitative process evaluation that explored health-care professionals' (HCPs') perceptions of delivering remote and face-to-face support to patients using POWeR+. Process evaluations are recommended in national guidance, 45 and can help to identify how health care is implemented: the likely mechanisms through which an intervention produces an effect and important factors within the health-care context that might influence the delivery and functioning of an intervention. We were particularly interested in understanding what it was like for HCPs to provide support for patients using POWeR+, as this could tell us more about whether or not the intervention might be feasible to implement in primary care, and could highlight any modifications that would be important to ensure its success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapter 5 Qualitative study with health professionals T his study presents a qualitative process evaluation that explored health-care professionals' (HCPs') perceptions of delivering remote and face-to-face support to patients using POWeR+. Process evaluations are recommended in national guidance, 45 and can help to identify how health care is implemented: the likely mechanisms through which an intervention produces an effect and important factors within the health-care context that might influence the delivery and functioning of an intervention. We were particularly interested in understanding what it was like for HCPs to provide support for patients using POWeR+, as this could tell us more about whether or not the intervention might be feasible to implement in primary care, and could highlight any modifications that would be important to ensure its success.…”
Section: Discussionmentioning
confidence: 99%
“…47 The CARe approach aims to provide an autonomy-supportive relationship, which can raise patients' autonomous motivation for behaviour change by promoting feelings of autonomy, competence (feeling effective) and relatedness (understood and cared for by others). 48 Autonomy-supportive relationships with HCPs predict better weight-loss outcomes, 45,48 as well as predicting outcomes in a range of other health conditions. 49 The theorised mechanisms of the CARe approach are explained in Table 35.…”
Section: Power+mentioning
confidence: 99%
“…The Sallis Support scales have adequate reliability and validity and have been utilized in previous weight loss studies (Gorin et al 2014). Two versions of the Sallis scales were administered -one for diet and one for physical activity-with participants asked to rate the behaviors of their partner participating in the study over the past 3 months.…”
Section: Exploratory Secondary Measuresmentioning
confidence: 99%
“…Research with general population samples has shown that family members and friends positively influence health behavior change in a variety of ways including practical support, verbal encouragement, exercising together, and by offering choices and options for healthy behaviors (Gorin et al 2014;Latkin and Knowlton 2015). Randomized controlled trials have shown that enrolling family and friends in weight loss programs leads to greater weight loss for participants, with the added benefit of weight loss among partners (Wing and Jeffery 1999;Gorin et al 2014). Support partners have been successfully trained to increase positive forms of social support (e.g., persuasion) while decreasing negative social support (i.e., criticism) toward participants enrolled in a lifestyle intervention (Sorkin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Se puede afirmar que los resultados obtenidos evidencian el vínculo de diferentes factores psicológicos protectores, en tanto estilos cognitivos asociados con conductas saludables y topográficamente medibles (como los mencionados en el texto), así como su aplicación práctica con miras a la formulación e implementación de programas de autocuidado en salud dirigidos a intervenir las condiciones de vida que determinan el riesgo de la población (31,36,39), contribuyendo a su vez a la creación de una cultura que refuerce los estilos de vida saludable (3,41). Así mismo, es deseable que dichos esfuerzos incluyan el fortalecimiento de dimensiones psicosociales como el crecimiento espiritual, la gestión adecuada de las relaciones interpersonales y el desarrollo de estrategias de afrontamiento ante situaciones estresantes (2,36,42), que permitan que las personas abordadas ajusten su pensamiento y manejo emocional hacia el desarrollo de conductas protectoras que contribuyan a reducir potencialmente situaciones prevalentes en salud pública con población adulta joven, especialmente estudiantes universitarios del área de la salud (41,42).…”
Section: Conclusiónunclassified